Comparative analysis of efficiency of different types of thermal insulation in heat exchanger-utilizer of heat loss recovery system of mobile compressor units - V. L. Yusha; G. I. Chernov; A. M. Kalashnikov (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
In this paper, a comparative theoretical analysis of the efficiency and applicability of some known types of thermal insulation in relation to the regimes typical for the MCU recovery systems is carried out. The study is carried out numerically by modeling heat transfer processes in the «coolant-wall-hot gas-snack-insulationenvironment» system, i.e. in a simplified version of the recuperative heat exchanger. As the external insulation of the heat exchanger, four most common types of insulation are used: foam insulation materials, fibrous, vacuum and active water insulation